11 Effect of pre-hospital administration of unfractionated heparin in acute st-elevation myocardial infarction. (25th January 2018) - McGinley, C; Mordi, I; Kelly, P; Currie, P; Hutcheon, S; Koch, S; Martin, T; Irving, J
Abstract : Background: We studied the effects of pre-hospital heparin in primary PCI patients, on infarct artery patency and long-term mortality. Methods: Consecutive patients (n=1000) admitted to Ninewells Hospital, Dundee, from 2010–2014 for PPCI were allocated to two groups: 437 (44%) pre-hospital heparin (PHH) administered by paramedics, and 563 (56%) in-hospital heparin (IHH). A trained medical student assessed coronary flow at presentation and collected the data. Mortality status was ascertained at 30 days and 5 years. Cox proportional hazards regression models were generated. Results: The patient groups were similar, although PHH had shorter symptom onset-treatment time (187 min vs 251 min, p<0.001) and less cardiogenic shock (3.9% vs 8.0%, p=0.008). Initial coronary flow was not different between the groups. 30 day mortality in PHH was 2.5% vs 8.3%, p<0.001. Independent predictors of 30 day mortality were age (odds ratio 1.07, 95% CI: 1.04 to 1.09), cardiogenic shock (5.97, 3.33–10.69), radial access (0.53, 0.28–0.98) and pre-hospital heparin (0.33, 0.17–0.66) (figure 1). 5 year mortality in PHH was 13.0% vs 21.6%, p<0.001. Significant predictors of long-term mortality were age (1.07, 1.06–1.09), cardiogenic shock (3.40, 2.23–5.17) and pre-hospital heparin (0.68, 0.49–0.96). Conclusion: Pre-hospital heparin was associated with reduced short and long-term mortality after adjusting for important potential confounders.